2007
DOI: 10.1002/cncr.22726
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic illnesses on the use and effectiveness of adjuvant chemotherapy for colon cancer

Abstract: In MRI, the suppression of fat signal is very important for many applications. Multipoint Dixon based water–fat separation methods are commonly used due to its robustness to B0 homogeneity compared with other fat suppression methods, such as spectral fat saturation. The traditional Cartesian k‐space trajectory based multipoint Dixon technique is sensitive to motion, such as pulsatile blood flow, resulting in artifacts that compromise image quality. This work presents a three‐point Dixon water–fat separation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 68 publications
5
115
0
3
Order By: Relevance
“…However, there were no significant differences in other major toxicities, including severe nausea, vomiting, stomatitis, leucopoenia, fever or infection, or grade 3 or greater toxicity for people with and without diabetes (56 vs 57%). A third study of Veterans Administration (VA) patients with colorectal cancer undergoing surgical resection found a higher risk of acute myocardial infarction (p 00.01) and anastomotic complications (p 00.02) in persons with diabetes post-operatively [55]. Finally, a study of 5,330 stage III colon cancer patients from the SEER-Medicare database found that patients with [56].…”
Section: Cancer Treatment-related Complication and Chemotherapy Toxicitymentioning
confidence: 99%
“…However, there were no significant differences in other major toxicities, including severe nausea, vomiting, stomatitis, leucopoenia, fever or infection, or grade 3 or greater toxicity for people with and without diabetes (56 vs 57%). A third study of Veterans Administration (VA) patients with colorectal cancer undergoing surgical resection found a higher risk of acute myocardial infarction (p 00.01) and anastomotic complications (p 00.02) in persons with diabetes post-operatively [55]. Finally, a study of 5,330 stage III colon cancer patients from the SEER-Medicare database found that patients with [56].…”
Section: Cancer Treatment-related Complication and Chemotherapy Toxicitymentioning
confidence: 99%
“…The presence of comorbid illness is rated by physicians as one of the most important issues when considering treatment options [2]. A SEER-Medicare linked database study of 5,330 patients ≥67 years old with stage III colorectal cancer found that patients with preexisting diabetes, congestive heart failure, or chronic obstructive pulmonary disease were significantly less likely to receive adjuvant chemotherapy [23]. However, those patients with comorbid illness who did receive chemotherapy were just as likely to obtain a survival benefit from treatment.…”
Section: Reviewmentioning
confidence: 99%
“…For example, patients with severe chronic airways disease are unlikely to tolerate pneumonectomy for lung cancer, but may tolerate treatment that does not affect the lung and patients with severe renal impairment are unlikely to tolerate nephrotoxic chemotherapy but may tolerate other chemotherapy drugs. Several authors have reported that co-morbidity does not increase the frequency or severity of treatment complications in some circumstances [9,10]. In contrast, other studies have reported higher rates of complications among cancer patients with co-morbidity [11,12].…”
Section: Resultsmentioning
confidence: 99%